2016
DOI: 10.1016/j.jep.2016.10.076
|View full text |Cite
|
Sign up to set email alerts
|

Ziziphora tenuior L. essential oil from Dana Biosphere Reserve (Southern Jordan); Chemical characterization and assessment of biological activities

Abstract: These findings add significant information to the pharmacological activity of Z. tenuior, thus justifying and reinforcing the use of this plant in traditional medicine. Additionally, the antifungal and anti-inflammatory potential of the oil at non-toxic concentrations, opens new avenues for its further exploitation, for instance in health-care product development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…Various studies have shown that pulegone is the main ingredient in various Ziziphora species (20)(21)(22)(23)(24)(25); nonetheless, the percentage of pulegone in the present study is lower than that in other studies. Also, the concentration of 50 μg/ml of ZEO reduces the number and imposes morphological changes in HT-29 cells.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Various studies have shown that pulegone is the main ingredient in various Ziziphora species (20)(21)(22)(23)(24)(25); nonetheless, the percentage of pulegone in the present study is lower than that in other studies. Also, the concentration of 50 μg/ml of ZEO reduces the number and imposes morphological changes in HT-29 cells.…”
Section: Discussioncontrasting
confidence: 89%
“…In this study, the main extracted compounds were pulegone (24%), menthol (14%), and menthone (9%) [22]. Other studies showed a tumor suppressor mechanism so that P53 acts as a transcription factor for a set of proapoptotic proteins from the BCL family (Puma, Bid, Noxa, and Bax).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Phytochemicals including essential oils (EO) and plant extracts isolated from diverse flora have shown to be effective alternatives with a potential to form novel drugs that could effectively be used in the treatment of such kind of recalcitrant infections (Bakkali et al, 2008 ). The EO and its active components (EO-ACs) have been extensively exploited and described to have antimicrobial, anti-inflammatory and anti-oxidant activities and considered safe in terms of animal and human health usage (Tampieri et al, 2005 ; Alves-Silva et al, 2016 ; Darwish et al, 2016 ). According to a recent report, carvacrol showed antifungal activity against C. neoformans strains and thus could be a potent drug component (Nobrega et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plants from the Lamiaceae family had the best antifungal activity, including Lavandula dentata (0.045–0.07 mg/L) [ 21 ], Satureja macrosiphon (0.06–8 mg/L) [ 22 ], and Ziziphora tenuior (2.5 mg/L) [ 23 ]. Artemisia judaica (2.5 mg/L) from the Asteraceae family [ 24 ], Lawsonia inermis (2.5–12.5 mg/L) from the Lythraceae family [ 25 ], and Thymus vulgaris (12.5 mg/L) from the Lamiaceae family [ 26 ] likewise exhibited good antifungal activity ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%